CULTIVATION OF ETHICS IN EARLY CHILDHOOD - Kirana lesmi; Iim Khotimah; Nunun Darojatun; Desty Rara Pringgandinie; Kiki Abdul Muluk; R. Oke Andikarya (Ann Publisher, 2024)
Ki Hajar Dewantara argues that ethics education focuses on forming children's character, behavior, and personality through several good habits from early childhood to adulthood. This means that the moral education that Ki Hajar Dewantara refers to is not teaching theories about good and bad, along with their very complicated postulates. However, the habit of doing good that is practiced every day until the action becomes steady in the child's psyche so that the teaching of theory and postulates can be valuable as an affirmation and a means, not as an end. Community service activities are carried out at RA Persis Bandung City with the aim of gaining new knowledge or discoveries regarding the cultivation of ethical values. To develop knowledge from research findings regarding the cultivation of pre-existing ethical values. To test, prove, or validate the truth and knowledge from research on the cultivation of pre-existing ethical values. This activity instills to find out what ethical values are instilled in early childhood at RA Persis 3 Bandung City. To find out the driving factors and inhibiting factors in instilling ethical values in early childhood at RA Persis 3 Bandung City. To find out what improvement efforts are being made by teachers in instilling ethical values in early childhood at RA Persis 3 Bandung City